Dancing protein clouds : intrinsically disordered proteins in health and disease. - Uversky, Vladimir N. (Progress in molecular biology and translational science, 2020)
Dancing Protein Clouds: Intrinsically Disordered Proteins in Health and Disease, Part B, represents a set of selected studies on a variety of research topics related to intrinsically disordered proteins. Topics in this update include structural and functional characterization of several important intrinsically disordered proteins, such as 14-3-3 proteins and their partners, as well as proteins from muscle sarcomere; representation of intrinsic disorder-related concept of protein structure-function continuum; discussion of the role of intrinsic disorder in phenotypic switching; consideration of the role of intrinsically disordered proteins in the pathogenesis of neurodegenerative diseases and cancer; discussion of the roles of intrinsic disorder in functional amyloids; demonstration of the usefulness of the analysis of translational diffusion of unfolded and intrinsically disordered proteins; consideration of various computational tools for evaluation of functions of intrinsically disordered regions; and discussion of the role of shear stress in the amyloid formation of intrinsically disordered regions in the brain.